Interpretatively automated identification of circulating tumor cells from human peripheral blood with high performance - Li, Xiaolei; Chen, Mingcan; Xu, Jingjing; Wu, Dihang; Ye, Mengxue; Wang, Chi; Liu, Wanyu (Frontiers in Bioengineering and Biotechnology, 2023)
The detection and analysis of circulating tumor cells (CTCs) would be of aid in a precise cancer diagnosis and an efﬁcient prognosis assessment. However, traditional methods that rely heavily on the isolation of CTCs based on their physical or biological features suffer from intensive labor, thus being unsuitable for rapid detection. Furthermore, currently available intelligent methods are short of interpretability, which creates a lot of uncertainty during diagnosis. Therefore, we propose here an automated method that takes advantage of bright-ﬁeld microscopic images with high resolution, so as to take an insight into cell patterns. Speciﬁcally, the precise identiﬁcation of CTCs was achieved by using an optimized single-shot multi-box detector (SSD)–based neural network with integrated attention mechanism and feature fusion modules. Compared to the conventional SSD system, our method exhibited a superior detection performance with the recall rate of 92.2%, and the maximum average precision (AP) value of 97.9%. To note, the optimal SSD-based neural network was combined with advanced visualization technology, i.e. the gradient-weighted class activation mapping (Grad-CAM) for model interpretation, and the t-distributed stochastic neighbor embedding (T-SNE) for data visualization. Our work demonstrates for the first time the outstanding performance of SSD-based neural network for CTCs identification in human peripheral blood environment, showing great potential for the early detection and continuous monitoring of cancer progression.